Dental Clinic Service Management System for Thepha Hospital - Lamsub, Dinat (Journal of Science and Technology Songkhla Rajabhat University, 2021)
This research aims to develop the dental clinic service management system for Thepha Hospital Which is developed as a web application using PHP language in combination with HTML5 and MariaDB as its database management system. Users of the system is divided into 3 different roles: admin, dentists, and customers. The application can manage dentist data, customer data, period information, book a queue, record treatment, browse treatment history and report. This application can increase the efficiency of the dentist's services and more convenience for customers to book in queue for dental services. The evaluation of the system has shown a very good overall satisfaction level with a score of 4.64.